Development of a novel mini peptide-based bioreceptor for haloalkane detection - Daud, Nurul Hazwani (2018)
Haloalkanes are the reactants in pharmaceutical manufacturing, which can be found in the final active pharmaceutical ingredients (APIs) and in the waste as impurities. Due to their toxicity effect to organisms’ health, the concern towards haloalkanes is increased. The conventional detection method is time-consuming, costly, lab-based, difficult to operate and not practical for continuous monitoring. Thus, this increases the demand for a simple and rapid device for direct detection of the compounds. Haloalkane dehalogenase (HLD) can be used as the specific bioreceptor to detect the presence of haloalkanes. But, the uses of native HLD are less efficient at extreme condition. Therefore, this study aims to develop a mini protein of HLD as an alternative bioreceptor focusing on sensitivity and stability. A novel mini peptidebased bioreceptor based on HLD from Xanthobacter autotrophicus (PDB ID: 2DHC) as template was developed for haloalkane biosensor. Yet Another Scientific Artificial Reality Application (YASARA) software was utilized to create the mini proteins by downsizing approach. Residues were removed gradually to obtain the mini protein while retaining the three active site residues; Asp-124 (nucleophile), His-289 (base), Asp-260 (acid) and two halide stabilizing residues; Trp-125, Trp-175. Five mini proteins comprising 283 amino acids or less, with the highest binding energy (enzymesubstrate complex) and distance of less than 4 Å between Asp-124 and three haloalkanes were chosen as the best validated designs. The recombinant mini proteins were constructed using pET vector and Escherichia coli BL21 (DE3) as the expression vector and host, respectively. The smallest mini protein, with 86 amino acids (model 5) was chosen for His-tag affinity purification and subsequent analysis as it could be expressed in soluble form. No catalytic activity was detected with haloalkane substrate. Isothermal titration calorimetry (ITC) showed there was binding interaction between the mini protein and haloalkane. Thermal stability study with circular dichroism (CD) had proven the mini protein possessed higher Tm value at 83.73 °C than the native HLD at 43.97 °C. Optical sensor with tapered multimode glass fiber (TMMF) was fabricated. Protein was immobilized on TMMF with the action of aminopropyl triethoxysilane (APTES) and glutaraldehyde (GA). The interaction of haloalkane and the immobilized mini protein showed an increment of the UV absorption at 325 nm. Optical sensor proved that the mini protein could act as a potential bioreceptor. However, it demonstrated low sensitivity for haloalkane at 0.0002 μM-1 (R2: 0.9832) with limit of detection (LOD) at 80 μM and low stability. Thus, screen-printed carbon electrodes (SPEs) was used to look for the interaction via electrochemical sensor, to enhance the sensitivity and stability. To improve the stability, mini protein structure was mutated with cysteine at residues 49 and 78 to form a disulfide bridge. Bare SPE was modified with gold nanowires coated on the working electrode surface, followed by self-assembly of L-cysteine (Cys) and GA for protein immobilization. The interaction of the mutated mini protein immobilized on SPEs was studied and compared to native HLD immobilized SPEs as positive control. Electrocatalytic oxidation of haloalkane was examined with cyclic voltammetry (CV) and differential pulse voltammetry (DPV) at working potential 0.03 V and -0.1 V, respectively. Electrochemical impedance spectroscopy (EIS) was also performed to detect the binding interaction of haloalkane with the fabricated mutated mini protein. An electrochemical sensor with DPV analysis presented a more sensitive (0.2118 μM- 1, R2: 09741) detection with low LOD at 6 μM. The sensor also demonstrated good repeatability (RSD 4.3%) and reproducibility (RSD 5%) for haloalkane detection. The mutated mini protein based sensor with modified SPEs provided higher sensitivity and better detection of haloalkane than the native HLD. It can be a potential tool in haloalkane detection for immediate application.